A standardized framing for reporting protein identifications in mzIdentML 1.2. Issue 21 (23rd September 2014) - Seymour, Sean L.; Farrah, Terry; Binz, Pierre‐Alain; Chalkley, Robert J.; Cottrell, John S.; Searle, Brian C.; Tabb, David L.; Vizcaíno, Juan Antonio; Prieto, Gorka; Uszkoreit, Julian; Eisenacher, Martin; Martínez‐Bartolomé, Salvador; et al.
<x xml:space="preserve">Abstract</x> Inferring which protein species have been detected in bottom‐up proteomics experiments has been a challenging problem for which solutions have been maturing over the past decade. While many inference approaches now function well in isolation, comparing and reconciling the results generated across different tools remains difficult. It presently stands as one of the greatest barriers in collaborative efforts such as the Human Proteome Project and public repositories such as the PRoteomics IDEntifications (PRIDE) database. Here we present a framework for reporting protein identifications that seeks to improve capabilities for comparing results generated by different inference tools. This framework standardizes the terminology for describing protein identification results, associated with the HUPO‐Proteomics Standards Initiative (PSI) mzIdentML standard, while still allowing for differing methodologies to reach that final state. It is proposed that developers of software for reporting identification results will adopt this terminology in their outputs. While the new terminology does not require any changes to the core mzIdentML model, it represents a significant change in practice, and, as such, the rules will be released via a new version of the mzIdentML specification (version 1.2) so that consumers of files are able to determine whether the new guidelines have been adopted by export software.